THE INTENTION OF YOUNG GENERATION TO REDUCE PLASTIC PACKAGING WASTE THROUGH ONLINE SHOPPING: THE APPROACH OF PLANNED BEHAVIOUR THEORY - Safaa Naila Yunisa; S. Rouli Manalu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This study investigates the influence of Attitude Towards Plastic Waste, Subjective Norms Towards Plastic Waste, and Perceived Behavioral Control Towards Plastic Waste on Generation Z's intention to reduce online shopping activities using the Theory of Planned Behavior (TPB). A quantitative approach with cross-sectional survey design involved 250 Generation Z respondents in Indonesia selected through purposive sampling. Data were analyzed using PLS-SEM with SmartPLS 4. Findings indicate that Attitude (β = 0.653; P = 0.000) and Subjective Norms (β = 0.206; P = 0.000) positively and significantly influence intention, while Perceived Behavioral Control (β = 0.057; P = 0.205) does not. The model explains 66.5% of the variance in intention (R² = 0.665).